Anesthesia and analgesia for shoulder surgery - Ahmet Eroglu (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
The shoulder is very important for a vertical body position and cosmetic appearance particularly in women. The shoulder joint has the largest motion range of all joints in the human body. All of the shoulder procedures need adequate anesthesia and analgesia for both the comfort of the patients and an early use of rehabilitation exercise. In current clinical practice general anesthesia or nerve blocks like infiltration and interscalene can be used for shoulder surgeries. When compared the anesthesia and analgesia techniques for shoulder surgery we should consider the effectiveness of pain control, incidence of side effects, and patient satisfaction of the techniques.